Case Report: Home initiation of nocturnal non-invasive ventilation in two adolescents with Duchenne muscular dystrophy and comorbid autism spectrum disorder and ADHD - Weerkamp, Pien M. M.; Voermans, Mark; Finders, Moniek; Brouwers, Arno; Collin, Philippe; Klinkenberg, Sylvia; Hendriksen, Jos. G. M. (Frontiers in Pediatrics, 2025)
This case report describes initiation of Nocturnal Non-Invasive Ventilation in home settings for two adolescents with Duchenne Muscular Dystrophy and different neuropsychiatric and neurocognitive comorbidities: one has Autism Spectrum Disorder, and the other has Attention Deficit Hyperactivity Disorder, obsessive thinking and anxiety. This report emphasizes the need for a multidisciplinary team approach, incorporating medical, psychological and psychopharmacological interventions for successful Non-Invasive Ventilation implementation. Challenges include recognition of neuropsychiatric and neurocognitive comorbidities often seen in Duchenne Muscular Dystrophy. Lessons learned from these cases underscore the importance of: coordinated multidisciplinary efforts, early advanced care planning, accurate psychoeducation, cautious psychopharmacological interventions, and parental and patient involvement. To our knowledge, this is the first case report describing implementing Nocturnal Non-Invasive Ventilation in home settings in adolescents with Duchenne Muscular Dystrophy and neuropsychiatric and neurocognitive comorbidities. In conclusion, implementation at home can be successful and become a realistic target for each individual with Duchenne Muscular dystrophy.